2014
DOI: 10.1007/s00384-014-1854-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for perioperative blood transfusions in laparoscopic colorectal surgery

Abstract: Preoperative Charlson score, hemoglobin level, carcinoma, and lower rectum pathologies were found to be independent risk factors for PBT in patients undergoing laparoscopic colorectal surgery. Evaluation of these risk factors prior to surgery may be helpful in selecting the patients who could benefit from possible alternatives to perioperative allogeneic blood transfusion and help constitute guidelines for a more responsible use of these alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…15,16 Previous studies in the field of colorectal surgery have identified preoperative hemoglobin, medical comorbidities, and malignancy as significant factors associated with transfusion. 17 Abdominal surgical approach is associated with an increased risk of transfusion in comparison to…”
Section: Commentmentioning
confidence: 99%
“…15,16 Previous studies in the field of colorectal surgery have identified preoperative hemoglobin, medical comorbidities, and malignancy as significant factors associated with transfusion. 17 Abdominal surgical approach is associated with an increased risk of transfusion in comparison to…”
Section: Commentmentioning
confidence: 99%
“…It has been shown that a blood transfusion causes effects at multiple levels of the immune system. A number of hypotheses regarding the biologic activity of PBT have been considered, among them host immunomodulation and growth factor delivery from red blood cells, but no definitive mechanistic link has been established …”
Section: Introductionmentioning
confidence: 99%
“…These values include factors, such as hemoglobin levels, total blood loss, and operative time, which are traditionally believed to be predictive for administering a transfusion. 10, 11, 12, 13 …”
Section: Discussionmentioning
confidence: 99%
“…Comorbidities have widely been shown to be prognostic indicators for receiving a transfusion, and in this study, the significant difference of comorbidities between the “No Blood” and “Blood” groups supports this theory. 10, 14 …”
Section: Discussionmentioning
confidence: 99%